An Empirical Study of Policy Implementation of Thailand Talent Mobility Programme - Poolsak Koseeyaporn; Kittisak Kaweekijmanee; Arum Kitipongwatana; Oraphan Wiarachai (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2017)
This paper empirically examines the national policy deployment of talent mobility programme aiming to leverage innovation atmosphere in private sector as a part of national strategy to escape middle income country status. The main policy mechanism is to facilitate universities and research institutes to develop their internal regulations in accordance with the Cabinet approval such that their talents can be legally mobilised to conduct research or project in private companies for competitiveness improvement. Moreover, clearing houses or service centres were established to eliminate the gap between industry and university, whereas training programmes were also developed for capacity building purpose, especially for staffs in those centres. Lastly, facilitation resources such as management, research fund, and compensation were mutually supported by government agencies including National Science Technology and Innovation Policy Office and Office of the Higher Education Commission. Based on data collection from the talent mobility projects executed during 2014 to 2016, key success factors and barriers were observed and subsequently the policy recommendations were proposed for improving the programme implementation in future. Keywords: Talent Mobility, STI Policy, GEDP